2019
DOI: 10.1111/ijcp.13451
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of provider documentation patterns as a tool to deliver ongoing patient‐centred diabetes education and support

Abstract: Background Diabetes mellitus (DM) is one of the most common chronic diseases in the world. As a disease with long‐term complications requiring changes in management, DM requires not only education at the time of diagnosis, but ongoing diabetes self‐management education and support (DSME/S). In the United States, however, only a small proportion of people with DM receive DSME/S, although evidence supports benefits of ongoing DSME/S. The diabetes education that providers deliver during follow‐up visits may be an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…4 It is recommended by the Association of Diabetes Care and Education Specialists for patients newly diagnosed with diabetes to receive an initial education consultation by a Certified Diabetes Care and Education Specialist (CDCES) and at least annually thereafter to optimize the ability to self-manage. 5 Diabetes self-management education (DSME) is an effective way to help achieve optimal patient clinical outcomes and reduce health care costs. The National Standards for Diabetes Self-Management Education and Support define DSME as "the ongoing process of facilitating the knowledge, skill, and ability necessary for prediabetes and diabetes self-care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 It is recommended by the Association of Diabetes Care and Education Specialists for patients newly diagnosed with diabetes to receive an initial education consultation by a Certified Diabetes Care and Education Specialist (CDCES) and at least annually thereafter to optimize the ability to self-manage. 5 Diabetes self-management education (DSME) is an effective way to help achieve optimal patient clinical outcomes and reduce health care costs. The National Standards for Diabetes Self-Management Education and Support define DSME as "the ongoing process of facilitating the knowledge, skill, and ability necessary for prediabetes and diabetes self-care.…”
Section: Introductionmentioning
confidence: 99%
“…4 It is recommended by the Association of Diabetes Care and Education Specialists for patients newly diagnosed with diabetes to receive an initial education consultation by a Certified Diabetes Care and Education Specialist (CDCES) and at least annually thereafter to optimize the ability to self-manage. 5…”
Section: Introductionmentioning
confidence: 99%
“…Both people with diabetes and HCPs reported that people with diabetes were more actively engaged as a result of PRO. In this pilot study, HCPs used the PRO tool without detailed protocolized steps for agenda-setting, shared decision-making [ 60 ], goal-setting, or action-planning [ 61 ], so the visits involved a learning experience where they each identified relevant strategies to use.…”
Section: Discussionmentioning
confidence: 99%
“…In the second study, 20,21 we investigated whether providers delivered DSMES to adults with DM based on patient characteristics. We analyzed clinic notes of adults with diabetes that are stored in EHR.…”
Section: Study 2: Using the Codebook To Evaluate Provider Documentati...mentioning
confidence: 99%